HUBUNGAN KADAR ZINK SERUM DENGAN FUNGSI KOGNITIF PADA LANJUT USIA - Prabaningrum Widyasmoro Prasetyanti; Hexanto Muhartomo; Maria Immaculata Widiastuti (PERDOSNI, 2019)
THE ASSOCIATION BETWEEN SERUM ZINC LEVEL AND COGNITIVE FUNCTION IN ELDERLY PEOPLEABSTRACTBackground: Dietary food intake can influence brain function, including zinc that has its higher level at hippocampus and amygdala. The most vulnerable age group that were exposed to zinc deficiency is elderly people >60 years. Zinc deficiency can lead to cognitive dysfunction, so early detection is required.Aims: To analyze the association between zinc serum levels with cognitive function in elderly people.Method: This research is an analytic observational research with cross sectional design. The subjects were elderly who fulfilled inclusion and exclusion criteria in Tresna Wredha Nursing Home, Semarang from May 1st, 2017 to November 30th, 2017. The nutritionist evaluated the diet at nursing home by food recall, and the result of zink diet was poor. Basic data were collected by interviewing the respondents with questionnaire, zinc serum level taken, and cognitive function assessed using Montreal Cognitive Assessment (MoCA) at the same time. The data was analyzed by bivariate analysis, and multivariate test with independent sample Kruskal-Wallis test, considered significant if p<0.05.Result: There were 47 subjects, with 48.9% had <12 years duration of education, 6.4% with obesity BMI, 59.6% with hypertension, 14.9% were smokers, 31.9% had anemia, 34% had hypercholesterolemia and 8.5% subjects with hypoproteinemia. Based on serum zinc levels 6.4% of subjects had zinc deficiency, 83% had normal low serum zinc levels, and 18.6% had normal high serum zinc levels. There was significant association between zinc serum levels, education, and hypertension with cognitive function. Based on multivariate test, a low zinc serum level had 8 times the risk of experiencing cognitive impairment.Discussion: There was a correlation between zinc serum levels and cognitive function in elderly people.Keyword: Cognitive function, elderly people, zinc serum levelABSTRAKPendahuluan: Asupan makanan memengaruhi fungsi otak, termasuk zink yang banyak terdapat di otak terutama hipokampus dan amigdala. Kelompok usia paling rentan terhadap defisiensi zink adalah orang dewasa berumur >60 tahun. Kekurangan zink dapat menyebabkan gangguan fungsi kognitif sehingga diperlukan deteksi dini.Tujuan: Menganalisis hubungan kadar zink serum dengan fungsi kognitif pada lanjut usia.Metode: Penelitian ini merupakan observasional analitik dengan desain potong lintang. Subjek penelitian adalah lanjut usia yang memenuhi kriteria inklusi dan eksklusi di Panti Sosial Tresna Wredha, Semarang. Penelitian dilakukan mulai 1 September 2017 hingga 31 Januari 2018. Dilakukan perhitungan diet oleh ahli gizi dengan food recall, dengan hasil asupan zink kurang. Data diperoleh dengan wawancara, pemeriksaan kadar zink serum, bersamaan dengan penilaian fungsi kognitif menggunakan Montreal Cognitive Assessment Indonesia (MoCA-Ina). Analisis data dengan uji bivariat dan uji multivariat menggunakan uji independent sample Kruskal-Wallis, dianggap bermakna bila nilai p<0,05.Hasil: Terdapat 47 subjek, dengan persebaran subjek dengan lama pendidikan <12 tahun 48,9%, subjek obesitas 6,4%, subjek dengan hipertensi 59,6%, subjek perokok 14,9%, subjek dengan anemia 31,9%, subjek hiperkolesterolemia 34% dan subjek hipoproteinemia 8,5%. Didapatkan 6,4% mengalami defisiensi zink, 83% memiliki kadar zink serum normal rendah, dan 18,6% memiliki kadar zink normal tinggi. Terdapat hubungan bermakna antara kadar zink serum, lama pendidikan, dan hipertensi dengan fungsi kognitif. Analisis multivariat menunjukkan kadar zink serum yang rendah memiliki risiko 8 kali lebih besar untuk mengalami gangguan kognitif.Diskusi: Terdapat hubungan bermakna antara kadar zink serum dengan fungsi kognitif pada lanjut usia.Kata Kunci: Fungsi kognitif, kadar zink serum, lanjut usia